You wouldn't want to be a slave in ancient Greece! : a life you'd rather not have - Macdonald, Fiona; Antram, David, 1958-; Salariya, David (New York : Franklin Watts, 2000)
Looks at the life of a Scythian woman after she is captured and sold into slavery in Greece in the fifth century B.C.
Includes index.
5.1.
5.1
3-6
Keywords: Slavery -- Greece -- Juvenile literature; Slavery -- Greece; Slavery -- Greece